Biosafety and bioefficacy assessment of human mesenchymal stem cells: what do we know so far?. (6th March 2018) - Yong, Kar Wey; Choi, Jane Ru; Dolbashid, Asdani Saifullah; Wan Safwani, Wan Kamarul Zaman
An outstanding amount of resources has been used in research on manipulation of human stem cells, especially mesenchymal stem cells (MSCs), for various clinical applications. However, human MSCs have not been fully utilized in clinical applications due to restrictions with regard to their certain biosafety and bioefficacy concerns, for example, genetic abnormality, tumor formation, induction of host immune response and failure of homing and engraftment. This review summarizes the biosafety and bioefficacy assessment of human MSCs in terms of genetic stability, tumorigenicity, immunogenicity, homing and engraftment. The strategies used to reduce the biosafety concerns and improve the bioefficacy of human MSCs are highlighted. In addition, the approaches that can be implemented to improve their biosafety and bioefficacy assessment are briefly discussed.